2003
DOI: 10.1002/cncr.11583
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor‐C expression correlates with lymph node localization of human melanoma metastases

Abstract: BACKGROUND Melanoma metastasizes by different mechanisms comprising direct invasion of the surrounding tissue and spreading via the lymphatic or vascular system. Despite their clinical relevance, the molecular mechanisms that guide the route of spreading and localization of the metastases in different tissues are not well known. Recent studies in different tumor types have shown that vascular endothelial growth factor‐C (VEGF‐C), which displays a high specificity for lymphatic endothelium, is involved in tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 42 publications
2
69
0
4
Order By: Relevance
“…Indirectly, tumor-induced lymphangiogenesis is correlated with metastasis in a number of cancer models, including colorectal, breast, prostate, head and neck cancer, and melanoma [93][94][95][96][97][98][99], and expression of Semaphorin…”
Section: Lymphangiogenesis and Cancermentioning
confidence: 99%
“…Indirectly, tumor-induced lymphangiogenesis is correlated with metastasis in a number of cancer models, including colorectal, breast, prostate, head and neck cancer, and melanoma [93][94][95][96][97][98][99], and expression of Semaphorin…”
Section: Lymphangiogenesis and Cancermentioning
confidence: 99%
“…38-40 In human melanoma, increased intra- and peritumoral LVD as well as the lymphatic growth factor VEGF-C strongly correlate with metastatic dissemination. 17 , 33 , 41-43 Lymphatic vessels may support migration of tumor cells, but may also modulate immune cells, as recently demonstrated in primary tumors and draining LNs in mice, 24 , 25 , 44 raising the possibility that lymphatics mediate immune suppression and poor clinical outcome in cancer patients. 19 , 31 , 42 Because corresponding human data are missing, we performed a very wide IHC analysis.…”
Section: Discussionmentioning
confidence: 93%
“…A significant relationship between high VEGF-C and VEGF-D expression and poor prognosis has been reported in many different tumor types (Onogawa et al, 2004;Miyata et al, 2006;Shida et al, 2006;Mylona et al, 2007), although few studies have reported on VEGF-C expression and its prognostic significance in malignant melanoma (Goydos and Gorski, 2003;Schietroma et al, 2003), and to our knowledge, none have reported on the prognostic significance of VEGF-D in malignant melanoma. Mylona et al (2007) confirmed VEGF-C as an independent indicator of poor prognosis in breast carcinoma, and similar results have been shown for several cancer types (Herrmann et al, 2007;Mohammed et al, 2007).…”
Section: Prognostic Value Of Vegf-c Vegf-dmentioning
confidence: 87%